Nilai Filosofi Doa Dalam Ekonomi Syariah - Muhammad Khoirul Malik; Rokhmat Subagiyo (TSAQAFAH, 2020)
AbstractThis article describes the philosophical values of supplication (dua) carried out by each business actor and its relation in the context of carrying out islamic economics. As an inseparable part of the survival efforts of a Muslim, islamic economics practices cannot be separated from the ritual of dua as a need to get blessings and happiness in the world and the hereafter. Dua becomes an important element in the implementation of islamic economics in order to minimize the occurrence of behavior deviations, such as dishonesty, selfishness, cheating, and gain profits by justifying any means. An understanding of the philosophical value of dua for a Muslim is required in each of his economic activities, so that he is always aware and remains in the corridor of islamic economics implementation. The study concludes that dua has a philosophical value teaching every Muslim to pray (dua) in their economic activities. Knowledge of the philosophical value of dua in islamic economic practices is important, because religion requires people to remember good attitude and behavior, be honest, willing to work hard and be aware that the ultimate goal of economic activities is intended to get a blessing and happiness in life in the world and the hereafter.Keywords: Philosophical Values, Supplication, Business Actors, Islamic Economics. AbstrakArtikel ini menjelaskan tentang nilai-nilai filosofi doa yang dilakukan oleh setiap pelaku usaha dan relasinya dalam konteks menjalankan ekonomi syariah. Kegiatan ekonomi syariah sebagai bagian tak terpisahkan dari upaya keberlangsungan hidup seorang Muslim tidak dapat terlepas dari ritual doa sebagai kebutuhan untuk mendapatkan keberkahan, kebahagiaan dunia dan akhirat. Doa menjadi unsur penting dalam pelaksanaan ekonomi syariah guna meminimalisir terjadinya penyimpangan perilaku dalam kegiatan ekonomi syariah seperti ketidakjujuran, egois, kecurangan, dan meraih keuntungan dengan menghalalkan segala cara. Pemahaman terhadap nilai filosofi doa bagi seorang Muslim diperlukan dalam setiap kegiatan ekonominya agar selalu sadar dan berada pada koridor pelaksanaan ekonomi syariah yang benar. Hasil kajian ini menyimpulkan bahwa doa memiliki nilai filosofi yang mengajarkan kepada setiap Muslim untuk berdoa di setiap aktifitas ekonominya. Pengetahuan akan nilai filosofi doa dalam praktek ekonomi syariah yang diajarkan oleh agama menjadi penting, karena agama mengajarkan umat manusia selalu ingat kepada sikap dan perilaku yang baik, jujur, mau bekerja keras dan sadar bahwa tujuan akhir dari kegiatan ekonomi tersebut dimaksudkan untuk mendapatkan keberkahan serta kebahagiaan hidup (falâḥ) di dunia dan akhirat.Kata Kunci: Nilai Filosofi, Pelaku Usaha, Doa, Ekonomi Syariah.